The influence of ECM matrix on stem cell differentiation - Woo, Mun Wah (2016)
Embryonic stems cells (ESCs) hold great potential for regenerative medicine. However, the ability to drive ESCs differentiation into specific lineages remains a major challenge. Extracellular matrix (ECM) being an essential component of the stem cell niche influences stem cell behaviors. Classically, emphasis was placed on ECM biochemical roles and how it regulates intracellular signaling cascades to direct stem cell differentiation. Recent evidence suggests that the mechanical properties of ECM can influence stem cell differentiation through remodeling of the cytoskeletal organization. This project aims to investigate the effects of matrix-stiffness on stem cell differentiation and lineage preferences. In addition, the role of a small GTPase, Ras homolog gene family member A (RhoA), which has been well documented for its role in regulation of cytoskeleton, in stiffness-mediated ESCs differentiation. Mouse ESCs were cultured on semi-synthetic hydrogels of different stiffnesses (1, 2.5, 10 and 40kPa). Expression of germ layer markers were examined using reverse transcription polymerase chain reaction. Our results revealed that matrix-stiffness mediated germ layer specification. Additionally, we observed that RhoA expression positively correlates with matrix-stiffness. Nonetheless, RhoA functions in matrix-stiffness mediated stem cell differentiation remains weakly supported. ECM mechanical properties continue to be a critical factor to determine stem cell fate.